Estudo da imunoexpressão de proteínas envolvidas na transição epitélio-mesênquima em tumores de glândula salivar - Sena, Dáurea Adília Cóbe (2022)
Salivary gland tumors (SGTs) present remarkable clinical and biological complexity; therefore, many studies investigate the events involved in their progression. One of the dynamics involved in the tumor invasion of different types of carcinomas is the epithelial-mesenchymal transition (EMT). In this process, epithelial cells undergo a transition to a mobile mesenchymal state, favoring invasion and metastasis. Therefore, this research analyzed the immunohistochemical expression of E-cadherin, Twist1, Snail1, α-SMA, vimentin (VM) and matrix metalloproteinase 9 (MMP-9) in 90 SGTs cases; correlations among the biomarkers, as well as between the biomarkers and clinicopathological parameters were made. We selected 20 cases of pleomorphic adenoma (PA), 20 cases of mucoepidermoid carcinoma (MEC), 20 cases of adenoid cystic carcinoma (ACC), 10 cases of polymorphous adenocarcinoma (PAC), 10 cases of epithelial-myoepithelial carcinoma (EMC) and 10 cases of carcinoma ex-pleomorphic adenoma (CXPA). E-cadherin, Twist1, and Snail1 were analyzed in tumor parenchyma, observing the percentage of positive cells (PP) using scores ranging from 0 to 4, and the expression intensity (EI), whose scores were ranged from 0 to 3. The evaluation of MMP-9 was performed in tumor parenchyma and stroma, also evaluating PP and IE, both based on scores that ranged from 0 to 3. The labeling for α-SMA and VM was analyzed in stromal cells. Positive cells for α-SMA were counted in 10 fields and the mean was calculated. VM was evaluated qualitatively, using 4 scores according to EI and whether the labeling was diffuse or focal. Obtained data were analyzed using Statistical Package for Social Science, GraphPad Prism, and STATA software. The significance level of 5% was adopted for the statistical tests. Patients were mostly female, with a mean age of 49.8 years; the major salivary glands were the most affected anatomical site, mainly the parotid gland. A lower E-cadherin immunostaining was verified in PAs in comparison to malignant neoplasms of salivary glands (MNSGs). Low immunoexpression of Twist1 and Snail1 was observed in PAs. Regarding the nuclear expression of Twist1, it was found greater expression in malignant neoplasms than in PAs. Furthermore, Twist1 in the nucleus was correlated with cytoplasmic expression of E-cadherin in MNSGs. Regarding clinicopathological parameters, this protein was statistically related to higher chances of death. Low immunoexpression of Snail1 was evidenced among the MNSGs. However, in the analysis of CACs, greater nuclear expression was observed in the solid variant compared to the others. Expression of MMP-9 in parenchyma showed a positive correlation with cytoplasmic Twist1 and Snail1nuclear in MNSGs. MMP-9 also showed a positive correlation when comparing its immunoexpression in the parenchyma and the stroma. VM was presented as a biomarker to be considered in the clinical evaluation of patients since it showed a significant correlation between greater tumor size and a higher frequency of death. Furthermore, the high expression of this protein appeared as an independent predictive factor for worse overall survival (OS) rates. The evaluation of the rest of the clinicopathological factors showed advanced clinical stages as an indicator of independent prognostic value for lower rates of OS. For disease-free survival, these indicators were the location in the minor salivary gland and the presence of distant metastasis. Our results suggest that the EMT may be related to myoepithelial differentiation in PAs and tumor progression in MNSGs. Also, Twist1 and MMP-9 appear to play a greater role in the scenario of EMT in MNSGs; finally, VM might be used as a prognostic value indicator.